Foreword - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 1999)
The stage of development of sociological thought is grounded on the development of principles of scientific explanation and the ability to define current issues. However, in Lithuania the model of scientific sociology is not being followed: ‘sociology’ means, it might be said, an overview of the statistical data and repetitive calculations. The influence of the quantitative tradition is of special notice. However, it is the conceptual level that lacks attention – the level of comparative analysis and argumentation.